Metabolomics characterization of two saffron from Iran and China using GC–MS and LC–MS methods - Donglin Li; Wenhui Zuo; Shuo Ma; Renjie Li; Zhenfeng Ye (Journal of Analytical Science and Technology, 2024)
Abstract Saffron is a medicinally important species of the Iridaceae family. Saffron’s quality depends on the concentration of secondary metabolites. In this study, GC–MS and LC–MS were utilized to dissect the different metabolites profile of two saffron produced in Iran and China. As a result, a total of 325 differential metabolites (237 from LC–MS, 88 from GC–MS) were identified. These differential metabolites were grouped into the following categories such as lipids, alkaloids, amino acids, terpenoids, organic acids, and flavonoids in saffron from the LC–MS analysis. The differential metabolites mainly concentrated on metabolic pathways, nucleotide metabolism, purine metabolism, and flavonoid biosynthesis. In Iran vs. China, the category of flavonoids includes Styrene, Apigenin-7-O-(6''-p-Coumaryl)glucoside, Houpulin F, Apigenin-5-O-glucoside, Tiglic acid; 2-Methyl-2-Butenoic Acid, p-Cymene, and 2,4-Nonadienal, (E,E)-. The terpenoids including downregulated Cafestol, rhodomollein XI, inumakiol G, D-Limonene, Bicyclo[3.1.0]hexane, 4-methylene-1-(1-methylethyl)- and upregulated rhodomollein XI were significantly different identified in Iran vs. China. In conclusion, the saffron from different cultivation areas possess many metabolites that are beneficial for health, including lipids, alkaloids, amino acids, terpenoids, organic acids, and flavonoids. Thus, compared with Iran, saffron from China have a higher medicinal value. This study provides a direction for the subsequent development and utilization of saffron.